A case report of leishmaniosis with primary oral manifestation in a cat - Mestrinho, Lisa A.; Travancinha, Joana; Sobral, Cristina (Frontiers in Veterinary Science, 2022)
A case of leishmaniosis with primary oral manifestations was reported in a 10-year-old neutered domestic shorthair cat. The primary lesion was a maxillary nodular lesion, painful with spontaneous bleeding associated with advanced periodontal disease, which did not resolve with tooth extraction or periodontal treatment. Biopsy revealed chronic neutrophilic and macrophagic infections and amastigote forms of Leishmania sp and molecular tests were able to identify Leishmania infantum. Oral signs resolved after the initiation of etiologic treatment with allopurinol. Distinguishing oral signs of leishmaniosis from other oral inflammatory diseases is important, especially in endemic areas, and co-infections must be considered with any oral manifestations of this disease.